Rapid detection of predation of Escherichia coli O157:H7 and sorting of bacterivorous Tetrahymena by flow cytometry - Hernlem, Bradley J.; Ravva, Subbarao V.; Sarreal, Chester Z. (Frontiers in Cellular and Infection Microbiology, 2014)
Protozoa are known to harbor bacterial pathogens, alter their survival in the environment and make them hypervirulent. Rapid non-culture based detection methods are required to determine the environmental survival and transport of enteric pathogens from point sources such as dairies and feedlots to food crops grown in proximity. Grazing studies were performed on a soil isolate of Tetrahymena fed green fluorescent protein (GFP) expressing Escherichia coli O157:H7 to determine the suitability of the use of such fluorescent prey bacteria to locate and sort bacterivorous protozoa by flow cytometry. In order to overcome autofluorescence of the target organism and to clearly discern Tetrahymena with ingested prey versus those without, a ratio of prey to host of at least 100:1 was determined to be preferable. Under these conditions, we successfully sorted the two populations using short 5 to 45 min exposures of the prey and verified the internalization of E. coli O157:H7 cells in protozoa by confocal microscopy. This technique can be easily adopted for environmental monitoring of rates of enteric pathogen destruction versus protection in protozoa.